Investigating Student-Lecturer Interactions in EFL Classroom: A Speech Acts Analysis - Afifuddin, Afifuddin (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2024)
Within educational settings, the exploration of signals presents enough opportunities to analyze the dynamic exchanges between teachers and students. Gaining insight into the consequences of sign usage in educational settings can improve teaching methods and foster a greater understanding of the intricacies of human communication. This study investigates the complexities of speech acts in the process of learning the English language, with a specific emphasis on illocutionary speech actions between students and lecturers. Gathering data from 24 students, who were randomly selected from a single class, was done using Searle's taxonomy of speech acts. Verbal exchanges were documented and examined utilizing pragmatic analytic methodologies. The results demonstrate a prevailing reliance on representatives, underscoring a significant focus on effective communication skills and values. Directives, which are intended to influence the activities of listeners, are commonly used, while expressives and commissives are less frequently employed. This distribution highlights the central emphasis on the exchange of knowledge and the solicitation of information or actions during classroom interactions. The novel finding of this research is the recognition of a distinct hybrid speech act that incorporates components of representatives and directions. This indicates a fresh approach where students can effectively communicate information while also influencing their peers' comprehension and actions.